2019
DOI: 10.1016/j.appet.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

“Animals are friends, not food”: Anthropomorphism leads to less favorable attitudes toward meat consumption by inducing feelings of anticipatory guilt

Abstract: Why do people befriend animals, yet don't feel conflicted about eating some of them? Previous research on the "meat paradox" suggests that the dehumanization of meat animals plays a crucial role in attenuating the negative affective states that consumers may experience when consuming meat. However, relatively little is known about how the converse process, namely anthropomorphism, influences meat consumption. The current research provides evidence that anthropomorphizing meat animals through the friendship met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 84 publications
5
51
1
1
Order By: Relevance
“…In addition, a CFA was applied to conduct the latent common method factor test which further evaluated the potential problem of common method bias. We allowed all the items to load on their respective variables and on an unmeasured common method factor [68]. We then compared the "standardized regression weights" (β) in the model with the common method factor with those in the model without the factor.…”
Section: Common Methods Variancementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a CFA was applied to conduct the latent common method factor test which further evaluated the potential problem of common method bias. We allowed all the items to load on their respective variables and on an unmeasured common method factor [68]. We then compared the "standardized regression weights" (β) in the model with the common method factor with those in the model without the factor.…”
Section: Common Methods Variancementioning
confidence: 99%
“…Guilt may arise when individuals perceive that their actions have violated certain social standard or moral norms [67]. Regular purchase and consumption of conventional meat instead of organic one can make consumers feel guilty since they care about environmental quality and welfare of animals, and such action is against their moral and ethical standards [45,68]. Hence, consumers might want to purchase organic meat to avoid this negative feeling [45].…”
Section: Guilt About Consuming Conventional Meatmentioning
confidence: 99%
“…There have been few published interventions testing this latter approach. In one, Wang and Basso (2019) found that thinking of pigs in humanizing terms—a manipulation countering speciesism and the denial of animal mind—led individuals to have less favorable attitudes toward pork, to feel more guilty about consuming pork, and to be less likely to buy or eat pork.…”
Section: Future Directionsmentioning
confidence: 99%
“…Attributing human characteristics to animals makes it much harder for consumers to deny animal mind. Initial research already found promising results in this respect [ 21 ]. However, this research focused on pro-social behavior only and ignored the ability to suffer or experience pain.…”
Section: Introductionmentioning
confidence: 99%